Swallowing disorders in nursing home residents: how can the problem be explained - Nogueira, D.; Reis, E. (Clinical Interventions in Aging, 2013)
Background: The swallowing mechanism changes significantly as people age, even in the absence of chronic diseases. Presbyphagia, a term that refers to aging-related changes in the swallowing mechanism, may be linked to many health conditions and presents itself in distinct ways. Swallowing disorders are also identified as a major problem amongst the elderly population living in nursing homes. Methods: The study sought to determine the prevalence of swallowing disorders in nursing home residents, to identify the relationship between self-perceived swallowing disorders, cognitive functions, autonomy, and depression, and also to analyze which variables explain the score of the Dysphagia Self-Test (DST). For this purpose, the researchers chose to apply a survey conveying questions on demographic aspects, general health, eating and feeding, as well as instruments to assess functional performance and the 3 ounce Water Swallow Test. Results: The sample consisted of 272 elderly people living in eight nursing homes in Portugal. Six did not sign the informed consent form. Of the total, 29% were totally dependent, 33% were depressed, 45% had cognitive impairment, and 38% needed help with feeding. About 43% of the individuals reported having problems related to eating. Regarding the DST, 40% showed signs of dysphagia. With respect to the 3 ounce Water Swallow Test, 38% revealed at least one of the symptoms, wet voice being the most prevalent. Correlation measures showed that age had no linear association with the DST score although correlation with the Barthel Index and Mini Mental State Examination was found to be significant. A linear regression model was estimated with the DST score as the dependent variable and the MMSE and BI scores, gender, age, education, the Geriatric Depression Scale score, 3 ounce Water Swallow Test, and diagnosed conditions (such as neurological disorder, dementia, and cardiorespiratory problems) as explaining variables. Conclusion: Results showed a high prevalence of dysphagia signs amongst a nursing home population. For the purpose of the present study, both a subjective and an objective assessment were applied. Results pointed to a significant statistical relation between objective and subjective measures, thus indicating that a self-perception test should be included in the assessment of swallowing disorders in a nursing home population. Notwithstanding, it should not be used as a single or principal measure as it is influenced by the individuals' cognitive condition.